Optimal antithrombotic therapy in ischemic stroke patients with non-valvular atrial fibrillation and atherothrombosis: study protocol for a randomized controlled trial - Okazaki, Shuhei; Yamamoto, Haruko; Asakura, Koko; Omae, Katsuhiro; Maeda, Hirotada; Tanaka, Kanta; Yamamoto, Shiro; Hirano, Teruyuki; Iguchi, Yasuyuki; Sakaguchi, Manabu; Koga, Masatoshi; Ihara, Masafumi; et al. (Frontiers in Neurology, 2024)
Background The addition of antiplatelet therapy to anticoagulant therapy in patients with stroke with non-valvular atrial fibrillation (NVAF) and atherothrombotic disease may increase bleeding risk without reducing recurrent stroke risk. Aims To evaluate the clinical benefits of anticoagulant monotherapy compared to combination therapy with anticoagulants and antiplatelet agents. Methods and design This is an investigator-initiated prospective multicenter, randomized, open-label, parallel-group clinical trial. Patients with NVAF and atherothrombotic disease who have had a recent ischemic stroke or transient ischemic attack will be eligible to participate in this trial. Study outcomes The primary outcome is a composite of ischemic cardiovascular events, including cardiovascular death, ischemic stroke, myocardial infarction, systemic embolism, ischemic events requiring urgent revascularization, and major bleeding events within 2 years after randomization. Sample size estimates This study will enroll 400 patients, 200 receiving anticoagulant monotherapy and 200 receiving combination therapy. This sample size will provide 90% power (one-sided p = 0.025) to detect a risk reduction in outcome events within 2 years, assuming event rates of 13 and 27% for each group, respectively, and a 10% loss to follow-up at a 2.5% significance level with one-sided log-rank tests at an interim analysis and a final analysis. Discussion This will be the first study to assess the net clinical benefit of oral anticoagulant monotherapy in ischemic stroke patients with NVAF and atherothrombosis. Clinical trial registration https://clinicaltrials.gov/study/NCT03062319, NCT03062319; https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000029222, UMIN000025392; https://jrct.niph.go.jp/latest-detail/jRCTs051180202, jRCTs051180202.